Global Expansion of Linezolid-Resistant Coagulase-Negative Staphylococci - Gostev, Vladimir; Leyn, Semen; Kruglov, Alexander; Likholetova, Daria; Kalinogorskaya, Olga; Baykina, Marina; Dmitrieva, Natalia; Grigorievskaya, Zlata; Priputnevich, Tatiana; Lyubasovskaya, Lyudmila; Gordeev, Alexey; Sidorenko, Sergey (Frontiers in Microbiology, 2021)
Coagulase-negative staphylococci (CoNS) for long time were considered avirulent constituents of the human and warm-blooded animal microbiota. However, at present S. epidermidis, S. haemolyticus and S. hominis are recognized as opportunistic pathogens. Although linezolid is not registered for the treatment of CoNS infections, it is widely used off-label promoting emergence of resistance. Bioinformatic analysis based on Maximum-likelihood phylogeny and Bayesian clustering of the CoNS genomes obtained in the current study and downloaded from public databases revealed existence of international linezolid resistant lineages each of which probably had a common predecessor. Linezolid resistant S. epidermidis sequence-type (ST) 2 from Russia, France, and Germany formed compact group of closely related genomes with median pairwise SNP difference of less than 53 SNPs, a common ancestor of this lineage appeared in 1998 (1986-2006) before introduction linezolid in practice. Another compact group of linezolid resistant S. epidermidis was represented by ST22 isolates from France and Russia with median pairwise SNP difference of 40, a common ancestor of this lineage appeared in 2011 (2008 - 2013). Linezolid resistant S. hominis ST2 from Russia, Germany, and Brazil, also formed a group with high level genome identity with median 25.5 core-SNPs differences, the appearance of the common progenitor dates to 2003 (1996 - 2012). Linezolid-resistant S. hominis isolates from Russia demonstrated associated resistance to teicoplanin. Analysis of mid-point rooted phylogenetic tree of the group confirmed genetic proximity of Russian and German isolates, Brazilian isolates were phylogenetically distant. repUS5-like plasmids harboring cfr were detected in S. hominis and S. haemolyticus.